2020
DOI: 10.3390/ma13153259
|View full text |Cite
|
Sign up to set email alerts
|

Crack Growth Behavior of Additively Manufactured 316L Steel—Influence of Build Orientation and Heat Treatment

Abstract: The effects of build orientation and heat treatment on the crack growth behavior of 316L stainless steel (SS) fabricated via a selective laser melting additive manufacturing process were investigated. Available research results on additively manufactured metallic parts still require a substantial expansion. The most important issue connected with the metal properties after additive manufacturing are the high anisotropy properties, especially from the fatigue point of view. The study examined the crack growth b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Further, residual stress on other surface characteristics, such as corrosion behavior [49], wear rate, and microstructure evolution reported some controversy. Additionally, there are some new types of approaches in the measurement of residual stress of AM part suggested by Kluczy ński et al [94,95], which significantly affect the fatigue properties of AM-made 316L steel [96][97][98], which was shown in the co-authors' own work. Hence, more work is required to explore the residual stress influences on corrosion behavior, wear rate, and microstructure evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Further, residual stress on other surface characteristics, such as corrosion behavior [49], wear rate, and microstructure evolution reported some controversy. Additionally, there are some new types of approaches in the measurement of residual stress of AM part suggested by Kluczy ński et al [94,95], which significantly affect the fatigue properties of AM-made 316L steel [96][97][98], which was shown in the co-authors' own work. Hence, more work is required to explore the residual stress influences on corrosion behavior, wear rate, and microstructure evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, trends in professional AM system development are mostly focused on the manufacturing of final products [ 10 ]. It is strictly related to a huge amount of research works connected with AM process analysis and data about the influence of different factors on the mechanical properties of produced parts [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Present trends in professional AM systems development are mostly focused on the usage of that kind of technology in final products [10]. It is strictly connected with a huge amount of research works connected with AM process analysis and data about the influence of different factors on the mechanical properties of produced parts [11][12][13][14][15][16][17][18]. Verboeket et al [19] indicated that the form of AM technologies development allowed for growth in its direct usage for final product production.…”
Section: Introductionmentioning
confidence: 99%